2015
DOI: 10.1111/ele.12427
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity in cities needs space: a meta‐analysis of factors determining intra‐urban biodiversity variation

Abstract: Understanding varying levels of biodiversity within cities is pivotal to protect it in the face of global urbanisation. In the early stages of urban ecology studies on intra-urban biodiversity focused on the urban-rural gradient, representing a broad generalisation of features of the urban landscape. Increasingly, studies classify the urban landscape in more detail, quantifying separately the effects of individual urban features on biodiversity levels. However, while separate factors influencing biodiversity v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
543
0
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 839 publications
(664 citation statements)
references
References 88 publications
27
543
0
23
Order By: Relevance
“…Saito and Koike, 2013;Concepción et al, 2015), we re-acknowledge that many macroorganisms decline in diversity in cities relative to rural areas and that some species are absent in cities, resulting in changes in composition. Recent work (Beninde et al, 2015) has surveyed the causes of intra-urban biodiversity variation for a range of macroorganisms and found that, to a great extent, shifts in composition and declines in diversity in cities are due to the effects of habitat area and connectivity, with the most affected green spaces in cities being both small and disconnected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saito and Koike, 2013;Concepción et al, 2015), we re-acknowledge that many macroorganisms decline in diversity in cities relative to rural areas and that some species are absent in cities, resulting in changes in composition. Recent work (Beninde et al, 2015) has surveyed the causes of intra-urban biodiversity variation for a range of macroorganisms and found that, to a great extent, shifts in composition and declines in diversity in cities are due to the effects of habitat area and connectivity, with the most affected green spaces in cities being both small and disconnected.…”
Section: Discussionmentioning
confidence: 99%
“…Species-area relationships, with fewer species in smaller sites, have been observed for microbes (Green et al, 2004;Horner-Devine et al, 2004;Bell et al, 2005) in habitats such as tree holes owing to the greater potential for colonization and quantity and diversity of available resources and habitats. At least for macroorganisms, urban, habitat area has a positive influence on biodiversity (Basham et al, 2010;Shanahan et al, 2011;Beninde et al, 2015). If urban habitat patches act analogously to tree holes, we expect to find fewer microbial species in smaller habitats in cities.…”
Section: Introductionmentioning
confidence: 97%
“…Apart from urbanization gradient analysis, there are other ecological frameworks that are also useful in understanding the ecology of urbanized landscapes, e.g. patch dynamics or meta-analysis (McDonnell and Hahs 2008;Beninde et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Inverse distance weighing (IDW) method was used to zone the dispersion of the birds and mammals. In order to set conservational priorities, topographic, plant life and birds and mammals' dispersion maps were overlaid and the region was divided into three conservation levels (high, medium and low) by using Spatial analyst tool in ARCGIS software [8][9][10][11].…”
Section: Determining the Sensitive Conservative Site In Kolah Ghazi Nmentioning
confidence: 99%